Concentration polarisation minimisation in membrane channels through electro-osmotic mixing - Liang, Yong Yeow (2015)
Reverse osmosis (RO) promises to play an increasingly crucial role in water supply, especially via desalination. One of the major problems faced by RO technology is the decline in membrane performance due to concentration polarisation (CP) and fouling. CP increases the osmotic pressure gradient across the membrane, hence reducing the net driving pressure gradient. Moreover, CP increases the probability of fouling. An electro-osmosis technique is proposed in this thesis which has the potential to reduce CP because it induces the movement of fluid in the vicinity of membrane, thus improving mixing within the boundary layer and enhancing mass transfer. Computational Fluid Dynamics (CFD) is used to simulate steady and unsteady electroosmotic flow (EOF) in 2D unobstructed and obstructed channels. First, a mathematical simplification of EOF is developed that reduces the required computational load while retaining the model’s accuracy and physical meaning. It is shown that EOF can be mimicked using a slip velocity. The results from CFD are found to be in good agreement both with published data and with more rigorous simulation approaches. For steady EOF in unobstructed channels, the spatial variation in slip velocity is found to be the driver for mass transfer enhancement. For uniform-unsteady EOF in unobstructed channels, a sinusoidal time-varying electro-osmotic slip velocity has negligible effect on the time-averaged hydrodynamics and mass transfer, because the effect is nullified within the time oscillation period. Nevertheless, there are still benefits for using unsteady EOF for fouling reduction/prevention, as increases in slip velocity ii frequency and amplitude increase the maximum wall stress which is a proxy for fouling reduction. For unsteady EOF in spacer-filled channels, the simulation results show that an oscillating slip velocity has the potential to induce vortex shedding. This occurs when a resonant slip velocity frequency is used for Reynolds numbers near the transition from steady to unsteady flow.